INTELLIGENT, INNOVATIVE AND SUSTAINABLE INDUSTRY IN BULGARIA – PROSPECTS AND CHALLENGES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The report analyzes industrial transfor-mation through smart and sustainable growth, as well as building a culture of innovation in a new digital age. Innovative enterprises from Bulgaria are presented with their respective modern organizational structures and forms of innovative cooperation between them - Sofia Techpark, Trakia Economic Zone, Technological Park at the Technical University of Gabrovo. The barriers to innovation development of SMEs in Bulgaria are outlined. An example of a high technology center funded under the EU Operational Programs is presented. Answers to questions such as: what are the role of the innovation centers in the innovation ecosystem in Bulgaria; how to stimulate the transfer of talent between university and business; how the market for innovation of the future changes; why de-literacy is a factor of success; how to support innovation and digitization; what are the European policies in the field of innovation and digitization?